LASER DECORATIVE PROCESSING ON CLOTHES MADE OF JEANS FABRIC (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article explores the innovative use of laser technology in decorative processing of clothing made from jeans fabric. It investigates the methods and techniques employed, presents the results achieved, discusses the implications, and offers conclusions and suggestions for the future of sustainable fashion.